Prevalence of Anemia and Associated Factors among Infants and Young Children Aged 6–23 Months in Debre Berhan Town, North Shewa, Ethiopia - Molla, Abebaw (J Nutr Metab, 2020)
BACKGROUND: Anemia is a problem of both the developed and developing world, which occurs in all age groups of the population. Half of the anemia cases are due to iron deficiency and affects physical growth and mental development. Nevertheless, there is a scarcity of information about anemia and associated factors among infants and young children aged 6 to 23 months in low-income countries like Ethiopia. OBJECTIVE: The aim of this study was to assess the prevalence of anemia and associated factors among infants and young children aged 6–23 months. METHODS: A community-based cross-sectional study design was used among 531 mothers/caregivers-children pairs in Debre Berhan Town, North Shewa, Ethiopia, from February 1 to March 2, 2018. The cluster sampling technique was used to select the study participants. Sociodemographic data were collected from mothers/caregivers using pretested structured questionnaires. Hemoglobin levels were measured using a HemoCue analyzer machine (HemoCue® Hb 301, Ängelholm, Sweden). All relevant data were described using descriptive statistics such as frequencies, proportions, mean, and standard deviation. Odds ratio and 95% CI were estimated using binary logistic regression to measure the strength of the association between anemia and explanatory variables. The level of statistical significance was declared at P < 0.05. RESULTS: The overall prevalence of anemia was 47.5% (95% CI: 43.1–51.4%) of which 18.3% were mildly anemic, 25% were moderately anemic, and 4.1% were severely anemic. In multivariable logistic regression analysis, household food insecurity (AOR = 2.7, 95% CI: 1.6–4.5), unmet minimum dietary diversity (AOR = 2.5, 95% CI: 1.4–4.3), stunting (AOR = 2.3, 95% CI: 1.2–4.3), and underweight (AOR = 2.7, 95% CI: 1.4–5.4) positively associated with anemia while having ≥4 antenatal care visits (AOR = 0.5, 95% CI: 0.3–0.9) and met minimum meal frequency (AOR = 0.25, 95% CI: 0.14–0.45) had a protective effect against anemia. CONCLUSION: Generally, the study showed that anemia was a severe public health problem among infants and young children in the study setting. Antenatal care visit, meal frequency, dietary diversity, underweight, stunting, and food insecurity significantly associated with anemia. Therefore, efforts should be made to strengthen infant and young child feeding practices and antenatal care utilization and ensure household food security, thereby improving the nutritional status of children.